The dark side of sustainability orientation for SME performance - KAUTONEN, Teemu (Institutional Knowledge at Singapore Management University, 2020)
This article examines how a firm’s willingness to make trade-offs that favour sustainability over commercial goals attenuates the relationship between firm-level sustainability orientation and subsequent performance. The hypothesis development draws on stakeholder theory and the literature on mission and revenue drifts, while the empirical analysis is based on two waves of original survey data on Finnish manufacturing SMEs. We find that sustainability orientation is positively associated with performance only when the willingness to make sustainability trade-offs is low, whereas the relationship becomes negative when the willingness to make such trade-offs is high. Our findings thus suggest that the popular adage of doing well by doing good might only hold if doing good does not conflict with business interests. The results add to stakeholder theory by showing how conforming to stakeholder expectations can be good for business – but only if doing so does not seriously compromise the pursuit of profits.